Introduction - Jolly, Margaret (The Australian journal of anthropology, 1994)
There has of late been much debate about the relation of women, nationalism and ethnicity. This collection contributes to that debate in several ways. Firstly, it considers the ways in which gender and ethnicity are complicit, or more precisely how identities as women and as national/ethnic subjects are mutually created. Secondly, it ponders the relation between the colonial and the postcolonial in such discourses of gendered ethnicity. And finally it poses the tough question about the problematic relation beteen women as objects and subjects of both colonial and postcolonial discourses.